Socioeconomics status indicators of economics development in Vietnam-post- DOI MOI period - Eswaranathan, Ehambaranathan (2013)
Vietnam is a densely- populated nation located in South East Asia that in the last three decades has recovered from the ravages of war and its aftermath, The country has transformed from a centrally-planned economy to a market economy. Consequently, the Doi Moi (renovation) policy has been introduced and implemented since l986 and it has progressed Vietnam’s economy effectively with positive and consistent Gross Domestic Product (GDP) growth as well as with high inﬂux of Foreign Direct Investment (FDI). The literature review section explores the geographical and historical backgrounds and economic development of Vietnam chronologically since the pre Doi Moi period, but with the greater focus on the post Doi Moi period and its policy implementations, especially on Vietnam’s economic advancement Signiﬁcantly, the literature search indicates that research on the effect of individual factor of SES mainly on employment and education indicators which have proven its signiﬁcance on Vietnam’s economic development is in its infancy and inadequate. Thus, the purpose of this research is to primarily focus on the Socioeconomic Status (SES) that explores the level of education and the employment determinants towards the growth of Vietnam’s economic development after the introduction of Doi Moi program In particular, the thesis examines the concept of Socioeconomic Status (SES) as the key determining factors contributing to Vietnam’s economy as well as evaluates the Doi Moi policy and its economic renovation programs from 1986 up until the year 2010. The post Doi Moi studies have revealed that despite enjoying remarkable economic growth over the recent years, Vietnam still possesses a low competitive capacity, productivity, and quality. Currently, Vietnam still faces low GDP per capita, high poverty, high inﬂation rate and unstable currency. This study aims to provide guidance as well as reveals the strengths and weaknesses of the policy including providing possible solutions on Vietnam”s SES level for the local, foreign investors and the Vietnamese govemment. Therefore, this research employs a qualitative case study research methodology to evaluate the SES determinants towards Vietnam’s economic advancement during the post Doi Moi period. Both quantitative and qualitative data collection methods were also used. The results of this study have revealed that education and the employment level have transformed and improved tremendously since 1986 in Vietnam. However, there are several issues that have been identiﬁed by the researcher that could be a disruption to the Vietnam’s continuing economic growth such as the increase in the poverty rate in urban areas, poor education quality system and the shortage of highly skilled employees in Vietnam. Overall, the researcher recommends the education quality must be improved through teaching, reward, facilities and intemational collaboration as improving education quality can solve the current problems of the shortage of highly skilled employees in the relevant industries and employment markets. Signiﬁcantly, human capital investment should be regarded as a national agenda as education is the key tool for human resource development of the nation.